17=1-3b-5b

Simple and best practice solution for 17=1-3b-5b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17=1-3b-5b equation:


Simplifying
17 = 1 + -3b + -5b

Combine like terms: -3b + -5b = -8b
17 = 1 + -8b

Solving
17 = 1 + -8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '8b' to each side of the equation.
17 + 8b = 1 + -8b + 8b

Combine like terms: -8b + 8b = 0
17 + 8b = 1 + 0
17 + 8b = 1

Add '-17' to each side of the equation.
17 + -17 + 8b = 1 + -17

Combine like terms: 17 + -17 = 0
0 + 8b = 1 + -17
8b = 1 + -17

Combine like terms: 1 + -17 = -16
8b = -16

Divide each side by '8'.
b = -2

Simplifying
b = -2

See similar equations:

| 6+(n-4)=2(2n+13) | | 3*x^2+2=50 | | 10h-8h=h+25 | | 18=-4x-2+4 | | 44=4(n+3)+4n | | 3y-20=30 | | 9x8/9 | | 23g=7.13 | | 3x+6=-18-3x | | 4-(p-1)+4p+7=p+4 | | 9+12x=-24+x | | 12x+17=13x+8 | | 2[t-(9-2t)]=4(2t-4) | | 6x+5y-1=10 | | 7x+1=-6+8x | | -24+x=x+13 | | 4x+12=36-6x | | 6(-s-6)-3(6s-3)=s+8+3s | | 193=41*1+0.40x | | -1.4+(-5.7)= | | 6t-24=0 | | X+76+110=180 | | 8x+9(.25x)=10 | | -2+26x=25x | | 4*8.4+8*0.8=40 | | -3-s=4tj+19 | | 8(1.25-1.125x)+9x=10 | | 4*12+8*0.8=40 | | 24=m-15 | | 4*10+8*0.8=40 | | 4*4.6+8*0.8=40 | | 16x+12y=136 |

Equations solver categories